Employee Acceptance of a Four-Day Workweek - Fottler, Myron D. (Academy of Management Journal, 1977)
An experimental work schedule consisting of four 10-hour days (4/40) was initiated at a large metropolitan hospital. Interviews were conducted to determine which employee and job characteristics were related to acceptance of the 4/40 innovation. Unanticipated upgrading in the nature of some jobs was the major variable differentiating supporters from nonsupporters.